Inflectional Morphemes and Their Grammatical Functions in Owl City`s Album Ocean Eyes (2009) - Hidayat, Muhammad Raihan; Rosalinah, Yanti (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2026)
This study investigates the grammatical functions and stylistic implications of inflectional morphemes in Owl City’s Ocean Eyes album (2009). Employing a qualitative descriptive design, the research analyzes how these morphological markers contribute to the lyrical structure based on the framework of Fromkin, Rodman, and Hyams (2018). Data were collected from official song lyrics, resulting in 151 identified words containing inflectional affixes. The findings reveal a significantly uneven distribution: noun plural markers are the most dominant category (63.8%), followed by verb inflections (32.5%) and adjective inflections (approximately 4%). The high frequency of plural nouns creates the vast, concrete imagery characteristic of the